CHELATE COMPLEXES OF MALIC OR CITRIC ACIDS WITH IRON, MANGANESE AND ZINC AS A BIOLOGICALLY ACTIVE SUPPLEMENT FOR BROILER CHICKEN DIET - Natalya Kochetkova; Elena Yakovleva; Andrey Shaposhnikov; Tatyana Shevchenko; Ludmila Zakirova (Belgorod National Research University, 2016)
he aim of the present study was to define the effects of the various doses of biologically active supplement, which was consisted of iron, manganese, zinc malates and citrates, on muscle mass formation, blood morphological composition and protein metabolism in broiler chickens during the entire period of their growth. It is shown, that chelate complexes of the life-critical trance elements stimulated muscle mass accumulation, which was associated with more efficient expenditure of amino acids for protein biosynthesis in myocytes. Researched morphological blood parameters were within the normal range for broiler chickens. From the physiological and biochemical point of view, the using of citrate malates is preferable to citrates.